PENGELOLAAN KINERJA MANAJEMEN SUMBER DAYA MANUSIA PADA PT PLN PERSERO BINJAI - M. Sultan Arif Iskandar Sitepu; Randi Andika; Anggi Pratama (Ensiklopedia Education Review, 2021)
This research is entitled "Performance Management of Human Resource Management at PT PLN Persero Binjai". This study aims to find out how to improve performance management to deliver the best performance of employees, teams, and organizations. This research was conducted using a qualitative descriptive research method. The results of research that have been carried out show that Performance Management at PT PLN Persero has been running well and can be accounted for. PT. PLN Persero has also prepared efforts to improve employee performance management including: career paths, training, and performance appraisals. However, there are still obstacles and obstacles in carrying out these efforts. So that requires PT. PLN Persero work harder.Keywords: Management, Performance, Human Resources.